Underwater delayed plugging material as well as preparation method and application thereof

Through the mixed materials of plant fiber, expansive soil and cinder, the problems of underwater gate leakage plugging materials are solved and the large amount of use is large, achieving efficient and long-lasting sealing effect, and is suitable for long-term leakage plugging applications of underwater gates.

CN119263771APending Publication Date: 2025-01-07CHINA YANGTZE POWER +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411301505.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing gate leakage plugging materials are easily dispersed under water, resulting in poor sealing effect, large amount of use and long time, and are prone to fall off when the water level fluctuates, affecting the stable operation of the gate.

Method used

The mixed granular material consisting of plant fibers, expansible soil and cinders is used to prepare underwater delayed sealing materials through stirring, screening and drying. The water absorption and expansion properties of expansible soil and the entanglement effect of plant fibers are used to form a solid Block the skeleton to resist head difference and water level fluctuations.

Benefits of technology

It improves the sealing efficiency and effect of underwater gates, reduces the amount of cinder, extends the service life of the sealing material, ensures long-term leakage and water stop, and reduces the price and operation complexity of the sealing material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263771A_ABST
    Figure CN119263771A_ABST
Patent Text Reader

Abstract

The invention discloses an underwater time-delay plugging material and a preparation method and application thereof.The underwater time-delay plugging material is obtained by wet stirring and mixing, drying, crushing and screening 2% by mass of plant fiber, 30-36.5% by mass of expansible soil and 61.5-68% by mass of coal cinder, the maximum particle size of the coal cinder is 0.8-1.0 time of the pore diameter to be plugged, and the content of clay minerals in the expansible soil is larger than or equal to 67%. The underwater time-delay plugging material has a good skeleton structure, is expanded and sealed when encountering water, is entangled, resists shear and avoids erosion, the success rate and accuracy of underwater gate plugging are improved, and the gate plugging process is accelerated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of leakage plugging of engineering materials, and in particular relates to an underwater delayed plugging material and a preparation method and application thereof. Background Art

[0002] The gate is an important part of the hydraulic metal structure, and its safe and stable operation is related to the normal operation of the entire project. However, during the long-term operation of the gate, it is inevitable to encounter leakage problems. The gate leakage problem will affect the work progress of the maintenance personnel of the unit, flow channel and gate chamber; at the same time, if the leakage is too large, it will also cause damage to the equipment due to the frequent start and stop of the maintenance pump. At present, the commonly used gate plugging method usually uses coal slag plugging. It is thrown on the water surface of the gate, and it slowly sinks in the water with the help of its own weight. When it is close to the gate leakage point, it is absorbed into the leakage point due to the change in the flow state of the water flow, and gradually gathers, thereby achieving the plugging effect. However, the actual use of coal slag plugging has poor results. The actual coal slag throwing process did not adopt a certain grading, resulting in that after the large-size coal slag "sealed the door", there was no appropriate small-particle coal slag to plug the gap. In order to achieve the plugging effect, a large amount of coal slag had to be thrown at one time, and the plugging effect was achieved through random probability, resulting in a large amount of plugging materials and a long plugging time. In addition, due to the insufficient adhesion between the coal slag, when the water level fluctuates, the coal slag particles are very easy to fall off, causing leakage again.

[0003] Chinese patent CN118148084A discloses a device and method for throwing plugging materials for gates, the device includes a lifting device, a cable and a throwing device, the plugging material is placed in the throwing device, and then the throwing device is moved to the turbulent area of ​​the leaking point by using the lifting device, and the plugging material in the throwing device is thrown out through the throwing hole by using the water flow device, and the leaking point is retained with the water flow to perform the gate plugging work; wherein the plugging material is coal slag particles wrapped with bentonite. However, bentonite is a loose soil body with a certain degree of dispersion. If there is a continuous permeable channel between the plugging particles, it is easy to be dispersed under the action of high water pressure, resulting in permeation erosion and gradual failure.

[0004] Therefore, it is necessary to develop a material that can prevent dispersion and has a good underwater blocking effect to improve the blocking efficiency and blocking effect of underwater gates. Summary of the invention

[0005] In response to the above technical problems, the present invention provides an underwater delayed plugging material, a preparation method and an application thereof, which utilizes expansive soil in conjunction with fiber-entangled and cemented coal slag to form a mixed granular material, thereby avoiding the failure of expansive soil to disperse underwater and improving the plugging efficiency and effect of underwater gates.

[0006] In order to achieve the above object, the present invention provides an underwater delayed plugging material, which is composed of the following raw materials in percentage by mass: 2% plant fiber, 30-36.5% expansive soil and 61.5-68% coal slag.

[0007] Preferably, the particle size of the expansive soil is 35-200 mesh.

[0008] Preferably, the expansive soil is clay containing at least one of clay minerals such as montmorillonite, illite, and kaolinite.

[0009] Further preferably, the content of clay minerals in the expansive soil is ≥ 67%.

[0010] Preferably, the maximum particle size of the coal slag is ≤ 1.0 times the pore size to be blocked.

[0011] Preferably, the plant fiber is any one of seed fiber, straw fiber, leaf fiber and husk fiber.

[0012] Further preferably, the seed fiber is cotton fiber or kapok fiber, the leaf fiber is sisal fiber, and the husk fiber is coconut shell fiber.

[0013] Preferably, the calculation formula for the amount of expansive soil is m b =ρ b ×V p / δ, where V p is the pore volume between the coal slag particles used, ρ b is the bulk density of the expansive soil before the no-load expansion rate test, δ is the no-load expansion rate of the expansive soil, m b is the mass of expansive soil.

[0014] Further preferably, the V p The confirmation method is: c Pour the coal slag into a beaker with a scale; place the beaker on a vibration table to fully vibrate the coal slag particles, and then fix a heavy object on the top to prevent the particles from floating; weigh the entire device, peel it and add water. When the water submerges the top layer of coal slag particles, wait until the coal slag is fully saturated with water, and then add water to the mark on the upper layer of coal slag. Record the mass of water added twice m w ; According to the saturated water absorption rate of coal slag w s , minus the water content in the pores of the coal slag m c × w s , then the water volume V between coal slag particles is obtained w =(m w -m c × w s ) / ρ w , where ρw is the density of water, and then the pore volume V between the coal slag particles is determined p ≈V w .

[0015] The present invention also provides a method for preparing an underwater delayed plugging material, comprising the following steps: (1) Sieve the coal slag to obtain coal slag of different particle sizes, and select coal slag that meets the national standard "Standard for Geotechnical Test Methods" (GB / T50123), and the maximum particle size of the coal slag is ≤ 1.0 times the pore size to be blocked, and the minimum particle size is one grade smaller than the maximum particle size as raw materials; (2) soaking the coal slag of different particle sizes obtained by screening in step (1) in water and stirring them to obtain coal slag that is completely saturated with water; (3) Mix the fully saturated coal slag with fiber, expansive soil and water, and mix them evenly in a drum mixer equipped with several breaking plates; after passing through a spherical mold, air-dry in a sun room; finely crush and sieve the air-dried material to obtain an underwater delayed plugging material.

[0016] Preferably, the stirring time in step (2) is ≥ 30 min.

[0017] Preferably, the underwater time-delay plugging material after crushing and screening also includes grading materials of different particle sizes, and the grading index n=0.45.

[0018] Further preferably, the grading formula is ; In the formula, U d Indicates the cumulative percentage of particle size d corresponding to the sieve, d max The aperture of the leaking point can be selected, and n is the grading index.

[0019] The present invention also provides an application of the underwater delayed plugging material, which is an application in underwater gate plugging.

[0020] Preferably, when the underwater gate is blocked, the underwater time-delay blocking material is transported to the vicinity of the penetration point of the underwater gate and then allowed to contact with water.

[0021] The beneficial effects of the present invention are: 1. The underwater delayed plugging material obtained by mixing, screening, crushing and drying plant fibers, expansive soil and coal slag solves the problems of large amount of coal slag, low plugging efficiency and poor plugging effect when using single coal slag for plugging, and improves the plugging success rate of underwater gates.

[0022] 2. The expansive soil has excellent water absorption and expansion properties, the plant fiber has an entanglement effect, and the coal slag has rigid and hard properties, which can be used as a sealing skeleton. The skeletons bite each other to resist the effect of water head difference; the expansive soil coated on the surface of the coal slag seals the gaps between the coal slag after absorbing water and expanding; the plant fiber entangles the coal slag and bentonite to prevent the bentonite from being eroded by high water pressure after being dispersed in water, thereby achieving a sealing and water-stopping effect, so that the underwater delayed plugging material can achieve a good plugging effect.

[0023] 3. The bonding effect of expansive soil and the entanglement of plant fibers enable the plugging material to resist the hydrodynamic shearing effect during water level fluctuations, avoid the plugging material from falling off again due to water level fluctuations, and achieve long-term plugging and water-stopping effects.

[0024] 4. The underwater delayed plugging material is applied in combination with the method of placing it near the infiltration point before adding the material, which reduces the contact time with water. The underwater delayed plugging material comes into contact with water after arriving near the infiltration point to prevent it from being dispersed due to premature contact with water. This improves the success rate and accuracy of underwater gate plugging, accelerates the gate plugging process, and has strong practical value.

[0025] 5. The present invention has the advantages that the raw materials are simple and easy to obtain, the price is low, the amount of coal slag used is reduced, the plugging method is simple, and the plugging effect and efficiency are good, and it can be promoted and applied on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The present invention is a flow chart for preparing the underwater delayed plugging material.

[0027] Figure 2 Figures 2 and 3 are the plugging effect diagrams of different materials, in which A is a photo of the effect after coal slag plugging, B is a photo of the effect under the action of waves after coal slag plugging, C is a photo of the effect after plugging by the underwater delayed plugging material prepared in Example 2, and D is a photo of the effect after plugging by the underwater delayed plugging material prepared in Example 2 under the action of waves. DETAILED DESCRIPTION

[0028] The technical solution of the present invention is further explained below in conjunction with the accompanying drawings and specific embodiments. It is worth noting that the following embodiments are only preferred embodiments of the present invention and should not be understood as limiting the present invention. The protection scope of the present invention shall be based on the contents recorded in the claims. Any modification or replacement made by those skilled in the art to the technical solution of the present invention without creative work shall fall within the protection scope of the present invention.

[0029] In the following embodiments, the particle size of the coal slag in the underwater delayed plugging material is selected based on the model of the pore size to be plugged being 15 mm.

[0030] Example 1 Confirmation of the ratio of coal slag to expansive soil (1) 189.12 g of coal slag (m c ) is placed in a beaker with a scale, and then the beaker is placed on a vibration table to fully vibrate the coal slag particles, and then a heavy object is fixed on the top to prevent the particles from floating; (2) Weigh the entire device in step (1), remove the skin and add water. When the water covers the top layer of coal slag particles, wait until the coal slag is fully saturated with water, then add water to the mark on the top layer of coal slag. Record the mass of water added twice, m w is 199.02g; according to the saturated water absorption rate of coal slag w s , minus the water content in the pores of the coal slag m c × w s , then the water volume V between coal slag particles is obtained w =(m w -m c × w s ) / ρ w , confirm the pore volume V between coal slag particles p 199.02cm 3 ; (2) According to the free expansion rate test method corresponding to the Geotechnical Test Method Standard GB / T50123, the free expansion rate δ of bentonite with a montmorillonite content of 67% was measured to be 154%; (3) Calculate the optimal volume of expansive soil to be added to coal slag. The calculation formula is V b =V p / δ, the result is 129.23cm 3 ; (4) Calculate the optimal mass m of expansive soil added to coal slag b =ρ b V b =ρ b ×V p / δ, the result is 107.78 g; (5) Calculate the mass ratio of expansive soil and coal slag: Based on the sum of the mass of coal slag and expansive soil accounting for 98% of the total mass of the plugging material (since fiber materials are relatively light, they are uniformly mixed at a mass ratio of 2%), calculate the mass ratio of expansive soil and coal slag in the plugging material respectively. The calculation formula is as follows: r b =m b / (m b + m c )×98%=35.58%; r c =m c / (m b + m c )×98%=62.42%.

[0031] Example 2 An underwater time-delay plugging material, composed of the following raw materials in percentage by mass: 2% cotton fiber, 35.58% bentonite with a montmorillonite content of 67%, and 62.42% coal slag; Preparation method: (1) Based on the diameter of the hole to be blocked in the underwater gate model of 15 mm, the particle size range of the coal slag after crushing is determined to be 10-15 mm; (2) Soak the coal slag in water and stir for 30 minutes to obtain fully saturated coal slag; (3) Cotton fiber, bentonite, coal slag and water are wet-mixed according to the formula, and then placed in a blender to mix evenly, and the mixed wet material is broken up while stirring; the mixed wet material is passed through a spherical mold with a particle size of 200 mm, air-dried and finely crushed, and passed through 15 mm, 10 mm, 5 mm, and 2 mm sieves to obtain underwater delayed plugging materials with particle sizes ranging from 10-15 mm, 5-10 mm, and 2-5 mm, respectively; (4) According to the Andreaen formula, the underwater time-delay plugging material is mixed with a gradation index of n=0.45 to obtain a finished plugging material; the Andreaen formula is: ; In the formula, U d Indicates the cumulative percentage of particle size d corresponding to the sieve, d max The aperture of the leaking point can be selected, and n is the grading index.

[0032] Example 3 An underwater delayed plugging material is composed of the following raw materials in percentage by mass: 2% cotton fiber, 30% bentonite with a montmorillonite content of 67% and 68% coal slag, and the preparation method is the same as that of Example 2.

[0033] Example 4 An underwater delayed plugging material is composed of the following raw materials in percentage by mass: 2% cotton fiber, 36.5% bentonite with a montmorillonite content of 67% and 61.5% coal slag, and the preparation method is the same as that of Example 2.

[0034] Example 5 An underwater delayed plugging material is composed of the following raw materials in percentage by mass: 2% coconut shell fiber, 35.58% weakly expansive clay (40% kaolinite content + 11% montmorillonite content) and 62.42% coal slag, and the preparation method is the same as that of Example 2.

[0035] Example 6 An underwater delayed plugging material is composed of the following raw materials in percentage by mass: 2% rice straw fiber, 35.58% weakly expansive clay (40% kaolinite content + 11% montmorillonite content) and 62.42% coal slag, and the preparation method is the same as that of Example 2.

[0036] Comparative Example 1 A plugging material is composed of the following raw materials in percentage by mass: 35.58% bentonite and 64.42% coal slag, and the preparation method is the same as that of Example 2.

[0037] Comparative Example 2 A plugging material, the formula and preparation method are the same as those in Example 2, except that the mass percentage of cotton fiber is changed to 1%, and the amount of bentonite is changed to 36.58%.

[0038] Comparative Example 3 A plugging material, the formula and preparation method are the same as those in Example 2, except that the mass percentage of cotton fiber is changed to 3%, and the amount of bentonite is changed to 34.58%.

[0039] Comparative Example 4 A plugging material, the formula and preparation method are the same as those of Example 2, except that the maximum particle size of the coal slag in step (1) is changed to 7.5 mm, i.e., 0.5 times the diameter of the pore to be plugged, and the coal slag particle size of 5-8 mm is selected as the original material.

[0040] Comparative Example 5 A plugging material, the formula and preparation method are the same as those of Example 2, except that the maximum particle size of the coal slag in step (1) is changed to 18 mm, i.e., 1.2 times the diameter of the pore to be plugged, and the coal slag particle size of 10-20 mm is selected as the original material.

[0041] Comparative Example 6 A plugging material, the formula and preparation method are the same as those in Example 2, except that bentonite is replaced by an equal amount of polyacrylamide (PAM).

[0042] Comparative Example 7 A plugging material is composed of the following raw materials in percentage by mass: 2% cotton fiber, 20% bentonite with a montmorillonite content of 67% and 78% coal slag. The preparation method is the same as that of Example 2.

[0043] Comparative Example 8 A plugging material is composed of the following raw materials in percentage by mass: 2% cotton fiber, 45% bentonite with a montmorillonite content of 67% and 53% coal slag. The preparation method is the same as that of Example 2.

[0044] Example 7 The opening and closing of the gates of hydropower stations are affected by policies, and there is uncertainty about whether there is water leakage after the gates are closed, which brings difficulties to the actual on-site throwing and plugging test. For this reason, a self-made indoor model test cabin with a height of nearly 4m, reserved vertical long strip leakage holes, and lateral visibility is used to carry out the throwing and plugging test of equal amounts of materials to verify the advantages and disadvantages of various plugging materials. Since the type and smoothness of the leakage holes in the model cabin are slightly different from the actual ones, and the maximum water depth at the leakage hole of the model cabin is 3m, which is much smaller than the water depth at the actual gate leakage, there is a lack of sufficient water pressure to squeeze the plugging materials, so the leakage holes cannot be completely sealed during the model cabin test process. Therefore, this embodiment uses the time required for the water level to drop 20cm after the throwing material is thrown from the top of the model cabin to indirectly illustrate the advantages and disadvantages of various plugging materials. The longer the time required for the water level to drop 20cm, the better the throwing and plugging effect, and vice versa. The test results are shown in Table 1. A throwing hole is reserved on the top of the model cabin, and the throwing hole can be controlled to open and close. A 4L mineral water bottle filled with 2kg of sealing material is inverted at the throwing hole, the throwing hole on the top of the model cabin is opened, and the stopwatch is started. The sealing material falls freely from the throwing hole and is carried by the water flow to the vicinity of the leaking point of the gate. Due to the pressure difference inside and outside the leakage point, under the action of the surrounding water pressure, the sealing material is absorbed into the leakage point along the water flow and blocked in the leaking gap.

[0045] Table 1 Performance of plugging materials

[0046] The results show that the saturated permeability coefficient of the plugging material can be significantly reduced by adding an appropriate amount of montmorillonite-rich bentonite (Examples 2-4, Comparative Examples 1-5, Comparative Example 8); as the amount of bentonite added decreases or the swelling performance of the expansive soil decreases, the saturated permeability coefficient of the plugging material increases slightly (Examples 5-6, Comparative Example 7), but is still less than the saturated permeability coefficient of coal ash, indicating that the addition of expansive soil can better achieve the effect of sealing the gaps between coal ash particles.

[0047] The appropriate expansive soil incorporation rate has a significant effect on the cohesion of the material (Example 2, Comparative Examples 7-8). This is because the bentonite cohesion effect is not obvious at an extremely low incorporation rate, and too high an incorporation rate will reduce the effect of coal slag in the material. The corresponding 35.58% bentonite incorporation rate corresponds to the gap filling effect between 10~15mm coal slag particles. When the particle size decreases, the corresponding particle gap decreases, and the 35.58% bentonite incorporation rate will be too much. Similarly, when the particle size increases, the 35.58% bentonite incorporation rate will be too little. Inappropriate proportions of plugging materials will reduce the shear properties of the plugging materials (Example 2, Comparative Examples 4-5). Comparing Example 2-4 with Comparative Example 1, the incorporation of cotton fiber significantly improves the cohesion of the plugging material; a 2% cotton fiber incorporation rate can obtain higher material cohesion (Example 2, Comparative Examples 2-3) The material ratio of Example 2 can achieve the best plugging effect by throwing. When the water absorption and swelling performance of the expansive soil is not enough, the plugging effect is very poor (Examples 5-6, Comparative Examples 6-7, coal slag), but too high a bentonite dosage will also cause the density of the plugging material to be too high, the adsorption effect during the throwing process is large, the adsorption process is too long, the water level drops quickly during this process, and the plugging effect of throwing is weakened (Comparative Example 8); at the same time, due to the soft bentonite and the small particle size of the coal slag skeleton, part of the plugging material will be washed out of the leaking hole, thereby weakening the plugging effect of throwing (Comparative Example 4). At the same time, in order to explore the anti-wave (water level fluctuation) effect of the above-mentioned plugging materials, after the above-mentioned test was completed (the water level dropped by 20cm), a camera was set up at the side window and turned on, and the rapid drainage port at the bottom of the model cabin was opened at the same time. During the rapid drainage process, significant turbulence and water level fluctuations occurred inside the model cabin. It was observed that: compared with the case without water level fluctuation ( Figure 2 A), the coal slag has obvious particle peeling at the plugging point (such as Figure 2 B); Comparative Example 1 material showed very little particle peeling; the underwater delayed plugging material prepared in Example 2 showed almost no particle peeling (such as Figure 2 D), when there is no water level fluctuation ( Figure 2 C) is basically the same. It can be seen that the presence of expansive soil and fiber materials improves the bonding performance between plugging materials.

Claims

1. An underwater time-delay plugging material, characterized in that: The material is composed of the following raw materials in percentage by mass: 2% plant fiber, 30-36.5% expansive soil and 61.5-68% coal slag.

2. The underwater time-delay plugging material according to claim 1, characterized in that: The particle size of the expansive soil is 35-200 meshes.

3. The underwater time-delay plugging material according to claim 2, characterized in that: The expansive soil is clay containing at least one of clay minerals such as montmorillonite, illite, and kaolinite.

4. The underwater time-delay plugging material according to claim 1, characterized in that: The maximum particle size of the coal slag is ≤1.0 times the pore size to be blocked.

5. The underwater time-delay plugging material according to claim 1, characterized in that: The plant fiber is any one of seed fiber, straw fiber, leaf fiber and husk fiber.

6. The underwater time-delay plugging material according to claim 1, characterized in that: The calculation formula for the amount of expansive soil is m b =ρ b ×V p / δ, where V p is the pore volume between coal ash particles, ρ b is the bulk density of the expansive soil before the no-load expansion rate test, δ is the no-load expansion rate of the expansive soil, m b is the mass of expansive soil.

7. A method for preparing the underwater time-delay plugging material according to any one of claims 1 to 6, characterized in that: The steps include: (1) Sieve the coal slag to obtain coal slags of different particle sizes, and select coal slags with a maximum particle size ≤ 1.0 times the pore size to be plugged; (2) soaking and stirring the coal slag obtained by screening in step (1) to obtain coal slag that is completely saturated with water; (3) Mix the completely saturated coal slag with fiber, expansive soil and water, stir and disperse, air-dry in a mold, crush and sieve to obtain underwater delayed plugging material.

8. The preparation method according to claim 7, characterized in that: The stirring time in step (2) is ≥ 30 min.

9. An application of the underwater time-delay plugging material according to any one of claims 1 to 6, characterized in that: The application is application in underwater gate blocking.

10. The use according to claim 9, characterized in that: When the underwater gate is blocked, the underwater time-delay blocking material is transported to the vicinity of the penetration point of the underwater gate and then allowed to contact with water.

Citation Information

Patent Citations

  • Gate leaking stoppage material throwing device and method

    CN118148084A